Mapping psycholinguistic features to the neuropsychological and lesion profiles in aphasia. (March 2020) - Alyahya, Reem S.W.; Halai, Ajay D.; Conroy, Paul; Lambon Ralph, Matthew A.
Abstract: Naming and word retrieval deficits are two of the most persistent symptoms in chronic post-stroke aphasia. Naming success or failure on specific words can sometimes be predicted by the psycholinguistic properties of the word. Despite a wealth of literature investigating the influence of psycholinguistic properties in neuro-typical and clinical language processing, the underlying structure of these properties and their relation to the fundamental language components and neural correlates are unexplored. In this study, a multivariate data-decomposition approach was used to identify the underlying structure within a collection of psycholinguistic properties (word imageability, frequency, age-of-acquisition, familiarity, length, semantic diversity and phonological neighbourhood density) and their influence on naming accuracy was explored in a cohort of 42 participants with a diverse range of chronic post-stroke aphasia classifications and severities. The results extracted three principal psycholinguistic factors, which were best described as 'lexical usage', 'semantic clarity' and 'phonological complexity'. Furthermore, a novel approach was used to systematically relate the influence of these psycholinguistic properties to participants' neuropsychological and lesion profiles. The findings did not show a one-to-one mapping between psycholinguistic features and core language components. 'Lexical usage' was the only factor that showed a significant difference between fluent versus non-fluent aphasia groups in terms of the influence of this lexical factor on successful naming, and it was the only factor that was related to the pattern of patients' brain lesions. Voxel-wise whole brain lesion-symptom mapping identified left frontal regions, aligning with previous evidence that these regions are related to language production functions, including word retrieval and repetition. The evidence from the current study suggests that the functional locus of psycholinguistic properties is distributed across multiple language components rather than being localised to a single language element.